Interrelationships of Touch and Proprioception with Motor Impairments in Individuals with Cerebral Palsy: A Systematic Review. Issue 3 (June 2022) - Santana, Camila A. S.; dos Santos, Mariana M.; de Campos, Ana Carolina
Considering that somatosensory impairments may impact motor performance in individuals with cerebral palsy (CP), a better understanding of these relations is relevant to planning interventions. To synthesize research evidence to date on the interrelationships between the somatosensory functions of touch and proprioception with motor functions in persons with CP, we systematically searched Embase, CINAHL, PsycINFO, and Medline databases for studies relating these variables that were published in English from the inception of these databases to November 2020. We targeted the following content categories in our literature search: (a) cerebral palsy; (b) sensory functions; (c) tactile functions; (d) proprioception functions; and (e) motor functions. The selection, data extraction, and methodological quality assessment of these studies were performed in duplicate. We retrieved and analyzed information regarding the studies' methodological approaches and synthesized results. The 11 studies that met our inclusion criteria showed that, in individuals with CP, impairments in tactile discrimination, proprioception, and stereognosis are related to motor functions in terms of overall manual ability, grip strength, postural control and locomotion. Thus, clinical practitioners should attend to somatosensory aspects of motor impairment in individuals with CP. More research is needed to clarify the direction of these associations.